Effect of ions (K+, Mg2+, Ca2+ and SO42−) and temperature on energy generation performance of reverse electrodialysis stack. (10th November 2018) - Guo, Zhi-Yuan; Ji, Zhi-Yong; Zhang, Yong-Guang; Yang, Feng-Juan; Liu, Jie; Zhao, Ying-Ying; Yuan, Jun-Sheng
Abstract: For investigating the influence of coexisting ions (K +, Mg 2+, Ca 2+ and SO4 2− ), temperature and their synergistic effect on energy generation by reverse electrodialysis, two series of cells dividing with Yadeshi membranes are fed with different solutions at 10 °C, 25 °C and 40 °C. The presence of K +, Mg 2+, Ca 2+ and SO4 2− results in lower open circuit voltage, higher internal resistance and lower maximum power density, and the influence order of ions coexisting with NaCl is Ca 2+  > Mg 2+ (>SO4 2− ) > K + . With the temperature risen, the open circuit voltage and the internal resistance show a trend of increase and decrease respectively, resulting in a bigger power density. Based on the synergistic effect of coexisting ions and temperature, the maximum power density of the pure NaCl system shows a greater increment (0.15 W m −2 ) than that of NaCl-CaCl2 (0.10 W m −2 ) and NaCl-MgCl2 (0.11 W m −2 ) systems when temperature increases from 10 °C to 40 °C. Furthermore, the transport quantities of ions in each system increased with temperature at different degrees, and the uphill of Ca 2+ and Mg 2+ was more obvious, which can reasonably explain the different effects of temperature on the maximum power density. Moreover, these results are further verified when simulated concentrated seawater is used for both the Yadeshi- and Fujifilm membranes, and the Fujifilm shows better energy generation performance mainly due to a lower internal resistance. Graphical abstract: The coexisting ions (K +, Mg 2+, Ca 2+ and SO4 2− ) with NaCl and temperature variation have synergistic effects on energy generation performance of reverse electrodialysis stack. Highlights: The presence of K +, Mg 2+, Ca 2+ and SO4 2− has a negative impact on power density. The influence order of coexisting ions with NaCl is Ca 2+  > Mg 2+ (>SO4 2− ) > K + . Rising temperature would enhance the power density of reverse electrodialysis. Temperature affects less on power density in NaCl-CaCl2 or NaCl-MgCl2 than NaCl.